Investasi Terbaik: Menanamkan Kesejahteraan Mental pada Anak Usia Dini - Reska Khairunisa; Taopik Rahman; Risbon Sianturi (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
While cognitive and physical gains often dominate early childhood discussions, this article shifts the focus to mental well-being as a primary investment in a child's future. Through a review of existing literature, it highlights how emotional care, secure bonds, and positive environments lay the groundwork for lifelong resilience. The analysis demonstrates that early mental health support leads to better life quality and future productivity. Ultimately, the article advocates for a collaborative approach between parents and teachers to prioritize daily emotional engagement as the base of early education